The rapid diagnosis and effective inhibition of coronavirus using spike antibody attached gold nanoparticles. Issue 6 (3rd February 2021) - Pramanik, Avijit; Gao, Ye; Patibandla, Shamily; Mitra, Dipanwita; McCandless, Martin G.; Fassero, Lauren A.; Gates, Kalein; Tandon, Ritesh; Chandra Ray, Paresh
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of the coronavirus disease that began in 2019 (COVID-19), has been responsible for 1.4 million deaths worldwide as of 13 November 2020. Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of the coronavirus disease that began in 2019 (COVID-19), has been responsible for 1.4 million deaths worldwide as of 13 November 2020. Because at the time of writing no vaccine is yet available, a rapid diagnostic assay is very urgently needed. Herein, we present the development of anti-spike antibody attached gold nanoparticles for the rapid diagnosis of specific COVID-19 viral antigen or virus via a simple colorimetric change observation within a 5 minute time period. For rapid and highly sensitive identification, surface enhanced Raman spectroscopy (SERS) was employed using 4-aminothiophenol as a reporter molecule, which is attached to the gold nanoparticle via an Au–S bond. In the presence of COVID-19 antigen or virus particles, owing to the antigen–antibody interaction, the gold nanoparticles undergo aggregation, changing color from pink to blue, which allows for the determination of the presence of antigen or virus very rapidly by the naked eye, even at concentrations of 1 nanogram (ng) per mL for COVID-19 antigen and 1000 virus particles per mL for SARS-CoV-2 spike protein pseudotyped baculovirus. Importantly, the aggregated gold nanoparticles form "hot spots" to provide very strong SERS signal enhancement from anti-spike antibody and 4-aminothiophenol attached gold nanoparticles via light–matter interactions. Finite-difference time-domain (FDTD) simulation data indicate a 4-orders-of-magnitude Raman enhancement in "hot spot" positions when gold nanoparticles form aggregates. Using a portable Raman analyzer, our reported data demonstrate that our antibody and 4-aminothiophenol attached gold nanoparticle-based SERS probe has the capability to detect COVID-19 antigen even at a concentration of 4 picograms (pg) per mL and virus at a concentration of 18 virus particles per mL within a 5 minute time period. Using HEK293T cells, which express angiotensin-converting enzyme 2 (ACE2), by which SARS-CoV-2 enters human cells, we show that anti-spike antibody attached gold nanoparticles have the capability to inhibit infection by the virus. Our reported data show that antibody attached gold nanoparticles bind to SARS-CoV-2 spike protein, thereby inhibiting the virus from binding to cell receptors, which stops virus infection and spread. It also has the capability to destroy the lipid membrane of the virus.